Potential use of Lupinus exaltatus Zucc. (Leguminosae) as green manure in soils of Jalisco, Mexico - Zamora Natera, Juan Francisco; Zapata Hernández, Isidro (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The environmental impact generated by agriculture with excessive use of fertilizers has led to the search for alternatives to improve soil fertility. This study aimed to evaluate the potential of Lupinus exaltatus in terms of decomposition and mineralization of nitrogen (N) when incorporated into the soil as green manure (GM) and its effect on the growth of Triticum aestivum L. seedlings. Litter bags were used, with a total of 216 nylon bags (10 × 5 cm), in each bag were placed 5 g dry base of GM in the vegetative stage and flowering. Subsequently, the GM bags were placed separately Vertisol and Regosol soil at a depth of 5 cm; and every three weeks until the end of the incubation, three bags were recovered per treatment. For evaluation of the effect GM on T. aestivum growth experiment was established in pots with soil Regosol, it consisted of incorporating 50 and 34 g dry base of the GM (equivalent to 10 and 15 t.ha-1). The GM in the vegetative stage lost an average of 83,52 % of its initial weight, while in flowering the loss was 76,49 %, the mineralized N was higher in Regosol soil than in Vertisol with 74,02 % and 70,58 % respectively. The wheat seedlings presented 30 % more dry matter and N with GM than the control treatment. L. exaltatus had a rapid decomposition and mineralization of N in the first stages of incubation.